The Toarcian Oceanic Anoxic Event in the South Iberian Palaeomargin - Reolid, Matías (SpringerBriefs in Earth Sciences,, 2018)
This book presents the first overview of the Toarcian Oceanic Anoxic Event in the southern Iberian paleomargin, in the western Tethys. The study of catastrophic events that affected the ecosystems in the past is of great interest, because it offers the possibility of establishing models that can be applied to current and future environmental changes. The book provides comprehensive information on the changes in marine ecosystems in connection with a global massive extinction, the Early Toarcian, and with the deposition of black shales, global warming and a disruption of the carbon cycle. In addition, the book describes the incidence of this event in this part of the Tethys close to the connection with the Protoatlantic, the Hispanic Corridor. Special attention is paid to sedimentological and ichnological aspects, fossil content (macroscopic and microscopic), and geochemistry. It also presents the facies changes related to fragmentation of the shelf and the evolution to hemipel agic troughs and swells in this paleomargin. Lastly, it characterizes this anoxic event in under-researched outcrops from southern Spain and compares the findings with those in well-known sections from northern and central Europe. This book offers a unique resource for all researchers interested in the Toarcian Oceanic Anoxic Event, but also in oceanic anoxic events that occurred during the Mesozoic in general, because of their similarity to recent climatic changes.